2000
DOI: 10.2136/sssaj2000.6462038x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrogen Mineralization Influenced by Crop Rotation and Nitrogen Fertilization

Abstract: N made available to crops that follow legumes in rotation. An estimate of soil mineralizable N is needed to determine crop While fertilization guides use total organic matter and needs for N fertilizer. The objective of this research was to estimate previous crop as indicators of N mineralization for the soil net N mineralization in soils maintained in continuous corn (Zea mays L.) (CC), corn-soybean [Glycine max (L.) Merr.] (CS), and coming season, a variety of direct and indirect lab methcorn-soybean-wheat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 32 publications
9
84
0
2
Order By: Relevance
“…In the 5-10 cm layer, the mineralization rate was lowest in the CT system, but did not differ from the other management systems (Figure 2). These lower rates probably occurred due to the immobilization of N fertilizer by soil microorganisms, which influenced the mineralization of organic N negatively, supporting the results of Carpenter-Boggs et al (2000), obtained in crop rotation systems involving corn and soybean.…”
Section: Net Mineralization and Nitrification Ratessupporting
confidence: 84%
“…In the 5-10 cm layer, the mineralization rate was lowest in the CT system, but did not differ from the other management systems (Figure 2). These lower rates probably occurred due to the immobilization of N fertilizer by soil microorganisms, which influenced the mineralization of organic N negatively, supporting the results of Carpenter-Boggs et al (2000), obtained in crop rotation systems involving corn and soybean.…”
Section: Net Mineralization and Nitrification Ratessupporting
confidence: 84%
“…When N is less available, microbes actively mine recalcitrant organic matter to acquire it; whereas, in N rich environments, microbes can assimilate inorganic N without costly mineralization activity. Although the relationship between inorganic N availability and microbial activities have been reported to be both positive [50,51] and negative [52][53][54] in empirical studies mainly based on fertilization experiments in forests, wetlands, or agricultural land, a meta-analysis of Treseder [55] suggested that N addition reduced microbial biomass by 15% and, consequently, also microbial activities such as soil respiration. Those articles could provide a theoretical proof and empirical evidence supporting the decrease of net N mineralization under high NH4 + concentrations in the BAF.…”
Section: Restricted Net N Mineralization Under Nh4 + Rich Conditionmentioning
confidence: 99%
“…Diversos autores (TouchTon e hargrove, 1982, rice e SmiTh, 1984, PöTTKer e roman, 1994, lara caBezaS, 2001 afirmaram que a utilização de uréia no SPD não é uma fonte eficiente de N para o sistema devido a perdas por volatilização e, com o acúmulo de resíduos culturais em superfície com elevada relação C:N, favorece a imobilização do N pelos microrganismos do solo (carPenTer-BoggS et al, 2000).…”
Section: Introductionunclassified